2020
DOI: 10.1111/ajt.15756
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis lung transplant recipients are at increased risk for EBV-associated posttransplant lymphoproliferative disorder and worse survival

Abstract: Epstein-Barr virus (EBV)-associated posttransplant lymphoproliferative disorder(EBV-PTLD) is a serious complication in lung transplant recipients (LTRs) associated with significant mortality. We performed a single-center retrospective study to evaluate the risks for PTLD in LTRs over a 7-year period. Of 611 evaluable LTRs, we identified 28 cases of PTLD, with an incidence of 4.6%. Kaplan-Meier analysis showed a decreased freedom from PTLD in idiopathic pulmonary fibrosis (IPF)-LTRs (P < .02). Using a multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Last, the intent of this study was to perform a detailed genetic study in IPF-LTRs versus non-transplant IPF to assess for telomere-mediated disease, but not to evaluate all transplant outcomes that we and others have described in the IPF-LTR patient population. Indeed, important questions remain regarding optimization of immune suppression, for which data was not available for the entire cohort in our study, that balance susceptibilities to complications such as bone marrow dysfunction, viral infections and malignancy in IPF-LTRs in the context of telomeremediated disease (44).…”
Section: Discussionmentioning
confidence: 99%
“…Last, the intent of this study was to perform a detailed genetic study in IPF-LTRs versus non-transplant IPF to assess for telomere-mediated disease, but not to evaluate all transplant outcomes that we and others have described in the IPF-LTR patient population. Indeed, important questions remain regarding optimization of immune suppression, for which data was not available for the entire cohort in our study, that balance susceptibilities to complications such as bone marrow dysfunction, viral infections and malignancy in IPF-LTRs in the context of telomeremediated disease (44).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this may be largely due to the higher dose of methylprednisolone in the immediate postoperative period that our basiliximab protocol requires. We also previously reported that early post-transplant lymphoproliferative disease (PTLD) is associated with alemtuzumab induction, especially EBV-mismatched groups ( 10 ). Alemtuzumab is thought to cause stronger immunosuppression, and there was concern that it could increase malignancies and infections.…”
Section: Discussionmentioning
confidence: 84%
“…Latent membrane protein 1 can become apparent in patients with severe IPF, and in total IPF had been identified more frequently in EBV positive patients than in healthy control groups [ 49 ]. It was also reported that an EBV infection can increase the risk of lung cancer in IPF patients [ 50 , 51 ]. In addition, the effects of EBV infections on tumorigenicity, metastasis, and TRAIL-sensitivity of non-small cell lung cancer were reported [ 52 ].…”
Section: Methodsmentioning
confidence: 99%